2017
DOI: 10.14502/tekstilec2017.60.290-295
|View full text |Cite
|
Sign up to set email alerts
|

Needleless Electrospinning of PAN Nanofibre Mats

Abstract: Polyacrylonitrile (PAN) is one of the few waterproof polymers that can be spun from relatively safe solvents, facilitating the use of PAN nanofi bre mats in diverse medical and biological applications, such as tissue engineering and cell growth promotion. PAN, on the other hand, is signifi cantly harder to use in electrospinning than polyethylene glycol and other water-soluble biopolymers. In our recent study, we thus varied spinning and material parameters for PAN dissolved in dimethyl sulfoxide (DMSO) and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 14 publications
1
45
0
Order By: Relevance
“…Electrospinning makes it possible to create nanofiber mats from diverse materials, such as pure polymers [1][2][3], polymers blends, composite fibers from polymers and ceramics or metals [4,5], and cyclodextrins [6]. These can be used in diverse applications such as filters [7][8][9], biotechnology and tissue engineering [10][11][12], for energy harvesting and storage [13,14], or other "smart" functions [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrospinning makes it possible to create nanofiber mats from diverse materials, such as pure polymers [1][2][3], polymers blends, composite fibers from polymers and ceramics or metals [4,5], and cyclodextrins [6]. These can be used in diverse applications such as filters [7][8][9], biotechnology and tissue engineering [10][11][12], for energy harvesting and storage [13,14], or other "smart" functions [15].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other methods, such as electrodeposition [25,26], seed-mediated growth [27], magnetic field patterning of magnetic precursor inks printed on a substrate [28], or electrochemical deposition [29], electrospinning has the advantage Materials 2020, 13 of enabling preparation of large-scale nanofiber networks in short times without the necessity to use a cleanroom, highly sophisticated equipment, or highly toxic material, and is thus often used to prepare magnetic nanofibers [30][31][32][33][34]. Notably, polyacrylonitrile (PAN) can be spun from the low-toxic solvent DMSO [3], making the whole process relatively easy to handle and avoiding unnecessary environmental pollution. In contrast to other methods of producing magnetic nanofibers, electrospinning usually creates nanofibers with different bending radii and forms a nanofiber mat without or with only low-fiber orientation [35][36][37], resulting in much more complicated magnetic anisotropies than straight, even nanofibers [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…While a large number of biopolymers can be electrospun from water [6,7], only few waterresistant polymers can be spun from low-toxic solvents such as dimethyl sulfoxide (DMSO) [8]. Th is is one of the reasons why polyacrylonitrile (PAN) is of large interest in electrospinning, apart from its usability as a precursor for carbon nanofi bres [9][10][11]. Preliminary tests in our group showed that animal cells do not grow well on pure PAN nanofi brous mats although serum was added to the culture medium.…”
Section: Introductionmentioning
confidence: 99%
“…One of the typical materials often used as a precursor of carbon nanofibers is polyacrylonitrile (PAN) [12,13]. This polymer has the additional advantage of being spinnable from the low-toxic solvent dimethyl sulfoxide (DMSO) [14].…”
Section: Introductionmentioning
confidence: 99%